The dark side of being a pathologist: Unravelling the health hazards - Saima Khan (Indian Journal of Pathology and Microbiology)
Background: Pathologists are indispensable to the practice of medicine. Awareness of health hazards among pathologists is a crucial aspect of today’s time. Numerous occupational health risks are prevalent which are mostly ignored; for example, the association of microscope use for prolonged durations leading to the development of chronic pain syndromes has been acknowledged for nearly three decades, yet most pathologists are unaware about this hazard until after it transforms into a chronic health issue. The purpose of this study is to learn its prevalence in working pathologists, make them aware of the risks, discuss and encourage them to proactively integrate strategies which are preventive in nature into their daily routine lives. Objective: The aim of the study was to analyze the level of risk, knowledge, awareness and biosafety measures taken by the pathologists in their routine daily work life. Materials and Methods: The study was conducted in a developing country, Northern India, using a standard online 50-item questionnaire enquiring about routine practices. 450 participants were enrolled consisting of 360 pathologists and 90 residents of pathology. Results: Among the 450 enrolled study participants, 84.8% complained of musculoskeletal disorders (MSD), with the neck being the commonest location of pain. Furthermore, 74.8% reported visual refractive errors, among which myopia took the highest place. Work injuries were reported in 60% of participants. Intolerance reactions to chemicals especially formaldehyde was observed in 63.1%. Depression and burnout were reported in 42%. Conclusions: Although knowledge seems to be near adequate, there is a lack of implementation and a noticeable risk of health hazards namely musculoskeletal problems, injuries, visual disorders, and ergonomic issues in routine daily activities of pathologists.